Given Coordinates: x1 = 2 y1 = 2, x2 = -4 y2 = 5
Distance Formula: d = √(x2 − x1)2 + (y2 − y1)2
Substitute the given coordinates into the Distance Formula and Simplify:
d = √(-4 − 2)2 + (5 − 2)2
d = √(-6)2 + 32
d = √36 + 9
d = √45
d = √9 * 5
d = √9 * √5
d = 3√5
Therefore, the distance between the points (2, 2) and (-4, 5) is equal to 3√5
Note: As a decimal number, 3√5 ≈ 6.7082039324994
Distance Formula: d = √(x2 − x1)2 + (y2 − y1)2
Substitute the given coordinates into the Distance Formula and Simplify:
d = √(-4 − 2)2 + (5 − 2)2
d = √(-6)2 + 32
d = √36 + 9
d = √45
d = √9 * 5
d = √9 * √5
d = 3√5
Therefore, the distance between the points (2, 2) and (-4, 5) is equal to 3√5
Note: As a decimal number, 3√5 ≈ 6.7082039324994